Tokyo ghoul. 12 - Ishida, Sui (VIZ Media, LLC, 2017)
"The 4th Ward falls under attack by Assistant Special Investigator Arima of the Commission of Counter Ghoul. Amon finds a connection between the CCG and an underground lab seemingly designed to research turning humans into Ghouls. And an old partnership reforms that could spell trouble for the 20th Ward" -- Page [4] of cover.